An assessment of the precise products on static Precise Point Positioning using Multi-Constellation GNSS - Mohammed, Jareer; Moore, Terry; Hill, Chris; Bingley, R.M. (2018)
Precise point positioning (PPP) is highly dependent on the precise ephemerides and satellite clock products that are used. Different ephemeris and clock products are available from a variety of different organizations. The aim of this paper is to assess the achievable static positioning accuracy and precision when using different precise ephemerides from three analysis centres Natural Resources Canada (EMX), European Space Agency (ESA) and GeoForschungsZentrum (GFZ), using GPS alone, GLONASS alone, and GPS and GLONASS combined. It will be shown in this paper that the precise products are significantly affected by the time-base of the reference stations, and that this is propagated through to all the estimated satellite clocks. In order to overcome the combined biases in the estimated satellite clock, in the PPP processing, these clocks errors need to be handled with an appropriate variation in the estimated receiver clock. It will also be shown that the precise coordinates of the satellites differ between the analysis centres, and this affects the PPP position estimation at the millimetre level. However, all those products will be shown to result in the same level of precision for all coordinate components and are equivalent to the horizontal precision from a Global Double Difference (GDD) solution. For the horizontal coordinate component, the level of agreement between the PPP solutions, and with the GDD solution, is at the millimetre level. There is a notable, but small, bias in the north coordinate components of the PPP solutions, from the corresponding north component of the GDD solutions. It is shown that this difference is due to the different strategy adopted for the GDD and PPP solutions, with PPP being more affected by the changing satellite systems. The precision of the heights of the receiver sites will be shown to be almost the same across all the PPP scenarios, with all three products. Finally, it will be concluded that accuracy of the height component is system dependent and is related to the behaviour of antenna phase centre with the different constellation type.